Hubungan Pola Sarapan Pagi dan Aktivitas Fisik dengan Prestasi Belajar Siswa/Siswi SMA Negeri 1 Tungkal Jaya Kabupaten Musi Banyuasin Sumatera Selatan - Kharisma Agustia Saadah; Andicha Gustra Jeki; Iswanto Iswanto (Prosiding Seminar Kesehatan Nasional, 2025)
Adolescents are in a period of rapid growth and development, requiring adequate nutritional intake and balanced physical activity to support health and academic performance. Breakfast plays an essential role in providing energy for the brain, while physical activity contributes to physical fitness and cognitive function. This study aimed to analyze the relationship between breakfast patterns and physical activity with students’ learning achievement at SMA Negeri 1 Tungkal Jaya, Musi Banyuasin Regency, South Sumatra. Data collection was conducted from July 22 to 24, 2025. This study employed a cross-sectional design involving 58 tenth-grade students selected through random sampling. Data on breakfast patterns were obtained using a Food Frequency Questionnaire (FFQ), physical activity levels were measured using the Physical Activity Level (PAL) method, and learning achievement was assessed based on the average semester report card scores. Data analysis was performed using the Chi-Square test. The results showed that most students had a frequent breakfast pattern (96.6%), a moderate level of physical activity (60.3%), and good learning achievement (67.2%). Statistical analysis indicated a significant relationship between breakfast patterns and learning achievement (p = 0.041), as well as between physical activity and learning achievement (p = 0.000). These findings suggest that regular breakfast consumption and adequate physical activity play an important role in supporting students’ academic achievement. Therefore, promoting healthy breakfast habits and regular physical activity among adolescents is essential to enhance academic performance.